Women-led SMEs: Innovation and collaboration → performance?. Issue 3 (1st October 2020) - Ibáñez, María José; Guerrero, Maribel; Mahto, Raj V.
ABSTRACT: Scholars and practitioners recognize the importance of innovation and collaboration for enhancing business performance. Gender diversity also influences business performance, either directly or indirectly. Gender diversity in a board of directors improves companies' innovative performance and, consequently, their performance. However, research on innovation in women-led small and medium-sized enterprises (SMEs) is limited, which significantly restricts our understanding of the innovation–performance relationship in such businesses. Thus, in this study, using a sample of 503 women-led SMEs, we show that innovation is not a determinant of businesswomen's business performance. Our study provides insights into how women-led SMEs deciding to innovate or collaborate are unable to appropriate the benefits suggested in the literature.